Robust decentralized proof of location for blockchain energy applications using game theory and random selection - Merrad, Yacine; Habaebi, Mohamed Hadi; Islam, Md Rafiqul; Gunawan, Teddy Surya; Mesri, Mokhtaria (MDPI, 2022)
To combat the problem of illegal access to a service, several location proof strategies have been proposed in the literature. In blockchain-based decentralized applications, transactions can be issued by IoT nodes or other automated smart devices. Key pair encryption and private key signing have been defined mainly for human identification in blockchain applications, where users are personally and responsibly concerned about the confidentiality of their private key. These methods are not suitable for computing nodes whose private key is implemented in the software they run. Ensuring that transactions are issued by a legitimate sender with the proper credentials is a bigger concern in applications with financial stakes. This is the case with blockchain energy trading platforms, where prosumers are credited with tokens in exchange for their contributions of energy. The tokens are issued by smart meter nodes installed at fixed locations to monitor the energy inputs and outputs of a given prosumer and claim energy tokens on its behalf from a defined smart contract in exchange for the energy it feeds into the grid. To this end, we have developed a decentralized Proof-of-Location (PoL) system tailored to blockchain applications for energy trading. It ensures that automated transactions are issued by the right nodes by using smart contract-based random selection and a game-theoretic scenario suitable for blockchain energy trading.